If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(x-3)=2(x-15)
We simplify the equation to the form, which is simple to understand
5(x-3)=2(x-15)
Reorder the terms in parentheses
+(+5x-15)=2*(x-15)
Remove unnecessary parentheses
+5x-15=+2+*(+x-15+)
Reorder the terms in parentheses
+5x-15=+(+2x-30)
Remove unnecessary parentheses
+5x-15=+2x-30
We move all terms containing x to the left and all other terms to the right.
+5x-2x=-30+15
We simplify left and right side of the equation.
+3x=-15
We divide both sides of the equation by 3 to get x.
x=-5
| 2x+4=x-10 | | -16+2x=-24+13x | | X+9-4=17 | | 6x+2(1+2x)=4(-2+5) | | -0.4(-0.6)= | | 3w(w+2)=0 | | (x+2)(x+1)=10 | | -2(7m-8)-3=-5(1+4m)+8m | | 3x(2xy+3y-2x)= | | X-12=43 | | 5-5(6-5)= | | 6(1-4p)=-8(-4+4p)-2 | | 61-3x=13-9x | | -6x-3.2=-3x+4.4 | | -9(6+n)=-54 | | -4.3+(-9.3)= | | 3x^2y+5y=2x | | v=(3.14)(36)(16) | | 3(2x-1)-6(x-4)=-9 | | -8(1-2k)=8(k-3) | | 46+2=3(5x+1) | | (x^4)-(10x^3)+(21x^2)+40x-100=0 | | 5+16z-3=9z+93-6z | | 49-2x=9-7x | | 5a=2a+7 | | x=1.4-(1.2x) | | X+6.5=9.7 | | 5+3x=-2x | | -3+6v=3(3v+4) | | 4(5x+3)-5(2x+1)=27 | | 4x+9=40-3x | | 3(3x+1)=39 |